Stereolithography 3D printing development of 3D printing machine controller using the predefined closest-distance volume interpolator system - -, - (2019)
Recent advancement in 3D printing technology has led to the development of projection mask stereolithography 3D printing process. This process harnesses the power of UV light contour projection to cure photocurable resin. The contour projection is generated by slicing STL CAD model into layers of 2D contours which is then fed into the UV projection device layer-by-layer with respect to the build height. Generation of the layers are computationally intensive. Existing contour generation algorithm requires long computational time to generate the contour layers especially for high polygon models. This is because the existing approach has to slice and compute every single layer of the STL model before the printing process starts. In an effort to reduce the computational time, a new and faster algorithm is required. Thus, a real-time contour generation algorithm is presented in this research. The real-time contour generation approach instantly generates single layer of contour whenever the build height parameter is fed into the algorithm. The algorithm composes of multiple algorithms such as slicing algorithm, pixel line mapping algorithm, and the contour loop algorithm. The proposed slicing algorithm uses line-plane intersection model to generate arbitrary line segment when it receives an STL facet. These line segments are mapped based on the projection device display resolution by the pixel-line mapping algorithm. Then, the pixelated line segments are connected to form single/multiple contour loops using contour loop algorithm. The results of each algorithms are thoroughly evaluated. It is later found that the algorithms able to correctly generates the contour projection layers. Even with the high polygon STL model, the contour generation algorithm able to perform with less than 100 milliseconds computational time which is suitable for real-time application.